Lessons in building capacity in sexuality education using the health promoting school framework: From planning to implementation. Issue 2 (1st February 2016) - Ollis, Debbie; Harrison, Lyn
Abstract : Purpose: – The health promoting school model is rarely implemented in relation to sexuality education. This paper reports on data collected as part of a five-year project designed to implement a health promoting and whole school approach to sexuality education in a five campus year 1-12 college in regional Victoria, Australia. Using a community engagement focus involving local and regional stakeholders and with a strong research into practice component, the project is primarily concerned with questions of capacity building, impact and sustainability as part of whole school change. The paper aims to discuss this issue. Design/methodology/approach: – Using an action research design, data were collected from parents, students, teachers and key community stakeholders using a mixed methods approach involving surveys, interviews, document analysis and participant observation. Findings: – Sexuality education has become a key school policy and has been implemented from years 1 to 9. Teachers and key support staff have engaged in professional learning, a mentor program has been set up, a community engagement/parent liaison position has been created, and parent forums have been conducted on all five campuses. Research limitations/implications: – The translation of research into practice can be judged by the impact it has on teacher capacity and the students' experience. Classroom observation and more longitudinal research would shed light on whether the espoused changes are happening in reality. Originality/value: – This paper reports on lessons learned and the key enabling factors that have built capacity to ensure that sexuality education within a health promoting, whole school approach will remain sustainable into the future. These findings will be relevant to others interested in building capacity in sexuality education and health promotion more generally.